Information Systems Design and Intelligent Applications Proceedings of Fifth International Conference INDIA 2018 Volume 1 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Somanah, Radhakhrishna; Yang, Xin-She; Senkerik, Roman (Advances in Intelligent Systems and Computing, 2019)
XIV, 560 p. 296 illus., 202 illus. in color.